2018
DOI: 10.4066/biomedicalresearch.29-17-3202
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation response index (SIRI) as a predictor for predicting inflammatory bowel disease (IBD) severity

Abstract: Peripheral venous blood markers may reflect the systematic inflammatory response condition. Various indices have been used to evaluate Inflammatory Bowel Disease (IBD), however, there is no ideal maker to assess the IBD activity and severity. We aim to investigate the potential value of Systemic Inflammation Response Index (SIRI) in IBD patients, and use it to predict the disease activity and severity. We designed a retrospective study to evaluate the SIRI in estimating disease severity in patients with IBD. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our research revealed statistically significant differences higher SIRI values in the S UC group compared to the Mi group, and higher SII values in the E3 group compared to the E1 group. The SIRI was formulated by YU et al [29], using the peripheral venous blood neutrophil, monocyte, and lymphocyte counts. The authors indicated that higher SIRI levels were significantly correlated with active inflammatory bowel disease (IBD), CRP, ESR, NLR, and MLR, and might be a novel promising marker of the disease severity in IBD.…”
Section: The Inflammatory Status Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research revealed statistically significant differences higher SIRI values in the S UC group compared to the Mi group, and higher SII values in the E3 group compared to the E1 group. The SIRI was formulated by YU et al [29], using the peripheral venous blood neutrophil, monocyte, and lymphocyte counts. The authors indicated that higher SIRI levels were significantly correlated with active inflammatory bowel disease (IBD), CRP, ESR, NLR, and MLR, and might be a novel promising marker of the disease severity in IBD.…”
Section: The Inflammatory Status Biomarkersmentioning
confidence: 99%
“…Noteworthy are the following hematological markers of systemic inflammation derived from the complete blood count panel (CBC): neutrophil-to-lymphocyte ratio (NLR), which highlights leukocytosis and lymphopenia in its initial inflammatory stage; monocyteto-lymphocyte ratio (MLR), which contributes to the body's immune status, with a decrease in its value indicating an immune dysfunction of the host; platelet-to-lymphocyte ratio (PLR), which is an inflammatory marker for diseases which are immune-mediated, metabolic, and pro-thrombotic in nature; the derived neutrophil-to-lymphocyte ratio (dNLR) (neutrophils/(white blood cells-neutrophils)), and the aggregate index of systemic inflammation (AISI) ((neutrophils × monocytes × platelets)/lymphocytes), which have been studied in Coronavirus disease-19 (COVID-19) [23,24]; the systemic immuneinflammation index (SII) ((neutrophils × platelets)/lymphocytes) [25][26][27][28]; and the systemic inflammatory response index (SIRI) ((neutrophils × monocytes)/lymphocytes) [29]. These hematological indices are considered to be faithful biomarkers for both sides of the inflammatory response, the innate immune system and the adaptive immune response, with increased sensitivity, accuracy, and availability, in addition to the traditional serological indicators (erythroyte sedimentation rate (ESR), fibrinogen (FIB), C-reactive protein (CRP) and white blood cell (WBC) count) [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%